MAKNA LIRIK LAGU INI JUDULNYA BELAKANGAN KARYA NOSTRESS SEBAGAI MEDIA KRITIK SOSIAL - Ahsan, Alfath Imam; Tandyonomanu, Danang (The Commercium, 2024)
This research is a study that contains an analysis of the lyrics of the song "Ini Judulnya Belakangan" popularized by a band from Bali, Nostress. In this study, researchers used qualitative methods with the approach of semiotics studies from Ferdinand De Saussure seen from signifiers and signifieds. In the process for data collection, researchers use document studies methods, content analysis and literature reference search. In this study, researchers took 6 verses of the analyzed songs. In the process, researchers find the message that the songwriter wants to convey. The lyrics of "Ini Judulnya Belakangan"contain many meanings such as social criticism, agrarian conflicts to efforts to save the environment, where the songwriter feels disappointment over what is happening around him. But on the other hand, songwriters also hope for a better future and try to remind their music listeners and the public to always be aware of what is happening around them and not be afraid to continue to speak out about various problems that are happening. Music is one of the media for delivering messages that can represent individuals or community unrest through lyrical lyrics created by musicians by looking at the reality that is happening which results in social criticism as done by Nostress.